Fabrication of zinc oxide film for carbon monoxide sensing - Dayrit, Jeriel Lloyd F.; Florido, Emmanuel A. (2015)
Zinc oxide (ZnO) films were successfully deposited on graphite substrate through electrophoretic deposition. Six samples were prepared using different applied voltages such that higher applied voltages resulted to higher mass of ZnO deposits and higher sensitivities at 26.5°C. The fabricated samples were reversible and more sensitive at greater carbon monoxide (CO) concentrations. Greater mass of film and higher CO concentration result to a better sensitivity because more ZnO particles and CO molecules can interact and contribute to gas sensing. Scanning election microscopy (SEM) revealed that the most and least sensitive samples (sample 6 and sample 1 respectively) were porous. Sample 6 had higher gas response than sample 1 due to its smaller particle size and thicket layer of deposits. Porosity and the size reduction of ZnO particles can enhance its sensing properties due to an increase of surface to volume ratio which allows more particles to perform in bulk gas interaction.
Keywords: Semiconductor films; Zinc oxide; Zinc oxide thin films